Percursos identitários do início da atividade profissional de uma professora de Matemática (Práxis Educativa, 2019)
A Mathematics teacher professional activity initiation identity pathways The main objective of this article is to understand the teaching initiation process of a mathematics teacher in her early career years. For this purpose, some Education doctoral research results are used, which was developed with the Paulista State University (UNESP), Faculty of Sciences and Technology, Presidente Prudente/SP - Brazil. The adopted methodology is qualitative and the data are centred on the quarterly interview scripts information, that sought to perceive in which direction the teacher was professionally self-developed, from her insertion in the career. Considering her perception analysis about the obtained formation in graduation and her early career construction, it is possible to conclude that, in this case, being a mathematics teacher implies a daily knowledge reconstitution, due to the complexity about teaching in public schools. Keywords: Formation and Identity. Teaching Beginning. Pedagogical Practice.